O uso de indicadores ácido-base naturais no ensino de Química: uma revisão - Almeida, Célio dos Santos (Brasil, 2021)
Acid-base indicators are substances that have different colors depending on the acidity of the solution that is present, being an alternative for the contextualization and elaboration of tests with accessible and low-cost materials. This manuscript aims to present a review on the use of natural products used as a natural indicator applied to the teaching of acid-base. The methodology consisted of an integrative bibliographic research, covering the period from 2010 to 2020. The research was carried out in a database Scielo, Google Scholar, Science Direct, ResearchGate, and Redalyc. There was an ample use of natural products obtained from flowers, fruits, roots, and leaves used as a natural indicator, showing the classes of flavonoids and anthocyanins as the main compounds associated with the ability to change color in different pH media. The presented data demonstrated the diversity of materials, which were efficient as a facilitating of students' learning, favoring the assimilation of the Chemistry contents through the contextualizing of theoretical knowledge. Keywords: Natural products; Chemistry Teaching; Anthocyanin.